Phenotypic Evaluation and Potential of Superior Varieties in Hybrid Watermelon (F1) from Single Cross - Anung Wahyudi; Yesika Tarigan; Ria Putri; Akbar Hidayatullah Zaini; Septiana Septiana; April Lia Sahidah (Green Engineering Society, 2025)
Superior hybrid watermelon seeds developed by university plant breeders are currently very limited, with most farmers relying on seeds from national seed companies. This research aims to identify the superior characteristics of watermelon plants, both qualitatively and quantitatively. This study employed a Randomized Block Design (RBD), with six F1 hybrid watermelon lines and four control varieties as factors. Data were analyzed using the F-test, and significant differences were further examined using the Least Significant Difference (LSD) test at the 5% level. Qualitative data were used to cluster analysis based on agronomic characteristics, calculated using NTSYS software. The results indicate significant variations in several morphological and agronomic traits among watermelon genotypes. Genotype WM 2210-1606 is superior in stem diameter, flowering time, and early harvest. Genotype WM 2210-1110 excels in vine and leaf length. GARNIS has the highest fruit weight, and WM 2210-1606 shows higher sugar content at the fruit's edge. Cluster analysis divides the genotypes into three main groups based on trait similarities. These variations highlight the potential for improving watermelon quality through breeding superior genotypes.